CodeSTEM: An Innovative Future Thinking-Based Coding Learning to Improve Students’ Computational Thinking Skills - Rati, Ni Wayan; Tri Esaputra, I Nyoman (Universitas Pendidikan Ganesha, 2025)
The lack of Computational Thinking skills and low motivation to learn coding in elementary schools pose a challenge in 21st-century education. This situation is exacerbated by the limited availability of innovative and contextual learning media that can support the development of these skills. This study aims to develop and test the effectiveness of the CodeSTEM learning platform based on coding with a Future Thinking approach to improve the Computational Thinking skills of seventh-grade elementary school students. The study uses a Research and Development (R&D) method with the ADDIE development model, which includes the stages of needs analysis, design, development, implementation, and evaluation. The needs analysis was conducted through literature review, observation, and interviews with teachers and students. Then, the platform was designed with interactive content that integrates Future Thinking and project-based learning. Product validation involved experts in content, design, and digital media to ensure theoretical and technical feasibility. Trials were conducted in stages: individual testing, small group testing, and field testing involving 28 fifth-grade elementary school students. Data were collected through observation, questionnaires, interviews, and pre-test and post-test assessments of Computational Thinking skills. Validation results showed that the product had very good feasibility, and the field test demonstrated significant improvement in students’ Computational Thinking abilities as well as positive responses to the media. This study contributes to the development of innovative and applicable digital learning media and serves as an effective alternative for coding education in elementary schools. Recommendations for further research include testing in broader contexts and developing offline features to overcome infrastructure limitations.